APLIKASI ALOFAN DALAM TANAH ANDISOL SEBAGAI ADSORBEN UNTUK MENURUNKAN BAKTERI Coliform LIMBAH CAIR DOMESTIK - Rois, Ibnu; Pranoto, Pranoto; Sunarto, Sunarto (EnviroScienteae, 2018)
Research on allophane has been done as an adsorbent to decrease MPN Coliform in domestic wastewater. The purpose of this study was to look for natural adsorbent materials that can be used to decrease MPN Coliform. Natural allophane was identified from andisol soil by pH analysis of NaF, FTIR, XRD, and SAA. The result of the analysis showed that there was allophane on andisol soil with pH 11,73. The diameter of empty space or alloy pores of 5 nm with a hole/pore size of 0.5 nm. Testing of MPN Coliform is done by method of Most Probable Number (MPN) variety 5: 5: 5. Based on the result of the research, allophane adsorbent can decrease MPN Coliform by 60.9%.